IMPLEMENTASI BLENDED LEARNING DI SMA PMB BANDUNG - Y.M. Azis; I. Hilman; G.N. Witka; R.I. Simanungkalit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The COVID-19 pandemic, which has begun to decrease the rate of transmission, does not necessarily mean that learning can be fully carried out face-to-face. Because of the fear of another pandemic making all parties have to keep anticipating what to do if this happens. Therefore to mitigate the negative impacts and ensure the continuity of learning, the learning process is carried out by means of blended learning. Blended learning must be carried out considering that it is impossible for students to learn fully independently. It takes several faceto-face meetings so that students have a place to ask questions, discuss with their teachers after they learn online. The priority problems for running blended learning are (1) the unavailability of smartphone-based applications owned by partners, (2) students and teachers do not understand e-learning and blended learning techniques, (3) teachers cannot design e-learning and blended learning programs. learning. The solutions provided are (1) modifying the e-learning application that has been used in research grants by the service team, so that it can be used on various types of smartphones and (2) providing training in making creative and innovative learning media designs. The results of this service activity are that students and teachers become accustomed to implementing blended learning, and teachers are able to design online-based learning media. Keywords: E-learning, blended learning, learning apllication